Educating the public about zoonoses through the Riley County Extension Agency: a field experience report - Bradford, Jessica (My University, 2014)
This report presents a detailed field experience undertaken for 240 hours with the Riley County Extension Agency. The mission of the agency is to make research from land-grant universities understandable and available to the public, who can then use the research to improve their homes, families, farms, businesses and communities. In 2009, a case of H3N2 influenza, a strain of “swine flu” was contracted by a child at the Riley County Fair. Because of that case, the Riley County Extension Agency has taken a particular interest in educating the public about infectious disease and zoonoses at the annual fair. Because the public comes into contact with many different species of livestock, the fair presents a unique opportunity to educate the public about zoonotic diseases of all domestic animals in a setting that encourages their interest. The experience of being in front of the public, representing the Riley County Extension Agency to the general public, refined my ability to make information relatable at many different education levels. Developing the display has not only deepened my understanding of zoonotic disease and food-borne illness but also strengthened my knowledge about how to educate both children and adults.
Keywords: H3N2 influenza; Swine flu; Zoonoses; Public Health (0573)